(untitled) (Dhaka University Law Journal, 2024)
In the recent past, there have been the cases of making abusive remarks against Prophet Muhammad, drawing cartoons of him, and burning the Holy Quran in public. These incidents no doubt outrage the religious feelings of people belonging to the religion of Islam. Besides this, they also contribute to violence and riot and the consequential deaths of people around the world. There are, however, literatures which seek to justify these conducts having a very liberal and extended view of the right to freedom of expression. They argue as if there should not be any limitation on freedom of expression so far that relates to contempt of any religion. I argue that freedom of expression howsoever valuable that might be, is a qualified as opposed to an unqualified human right. Hence, its exercise cannot extend to making abusive remarks against religious personages or defiling or burning the Holy Book(s) of any religion. If it is acknowledged by all including the relevant stakeholders of the United Nations, this might help reducing the chances of human casualties and deaths of people caused by alleged blasphemous conducts with respect to any religion. Foreseeing this significance, I aim to revisit the justification and limits of freedom of expression in the backdrop of contempt of religion. Dhaka University Law Journal, 2023, 34 (2), 43-65